CRIMINAL DISPENSATION AGAINST NARCOTIC ABUSES AND ADDICTIVES REVIEW FROM UU NO 35/2009 - Marasabessy, Fachrul (Islamic Banking & Economic Law Studies (I-BEST), 2022)
This writing examines or analyzes secondary data in the form of secondary legal materials by understanding law as a set of regulations or positive norms in the legal system that regulates human life (library research). Based on the results of the study, it is known that law enforcement against narcotics crimes according to the Narcotics Law is subject to imprisonment, fines, life imprisonment and other sanctions. , Narcotics circulation in terms of international law, namely the policy of dealing with narcotics crimes was originally stated in The United Nation's Single Convention on Narcotic Drugs 1961.